The importance of covalent coupling in the synthesis of high performance composite anodes for lithium ion batteries. Issue 51 (10th May 2016) - Zeb, Gul; Gaskell, Peter; Kim, Young Nam; Jalani, Ghulam; Xiao, Xingcheng; Szkopek, Thomas; Cerruti, Marta
Abstract : We present a direct comparison between identical electrostatically and covalently assembled Si–graphene composites for lithium ion battery anodes. Abstract : We present a direct comparison between identical electrostatically and covalently assembled Si–graphene composites for lithium ion battery anodes. The covalent composite is synthesized via amide bond formation between aminated Si nanoparticles and carboxylated graphene using carbodiimide as coupling agent. The composite exhibits 14 times higher reversible capacity retention after 100 lithiation/delithiation cycles in comparison with electrostatically coupled Si–graphene composites. The results indicate that covalent coupling of Si and graphene improves the nanoscale mechanical stability during cycling and improves electrical contact between graphene and Si, thus resulting in higher capacity retention.